Demonstration of a Plasmatic Cofactor Different from Fibrinogen Necessary for Platelet Release by ADP and Adrenaline - Cronberg, S; Kubisz, P; Caen, J. P (Thrombosis and Haemostasis, 1970)
Secondary wave production and release of platelet factor 4 were studied in washed platelet suspensions and citrate plasma. Induction of a secondary wave requires the presence of large aggregates and a plasmatic cofactor different from fibrinogen. Acetyl-salicylic acid inhibited the production of a second wave both in plasma and platelet suspensions. Plasma taken after the intake of acetyl-salicylic acid induced a second wave in platelets harvested before the intake. The possible production of thrombin or allied enzyme inside the platelet aggregates due to changed internal milieu is suggested as a possible cause of the release reaction induced by ADP and adrenaline. Fundamental differences existed between the release induced by ADP and adrenaline and that induced by collagen, kaolin and other particles.